Metabolic engineering against the arginine microenvironment enhances CAR-T cell proliferation and therapeutic activity - Fultang, Livingstone; Booth, Sarah; Yogev, Orli; Martins da Costa, Barbara; Tubb, Vanessa; Panetti, Silvia; Stavrou, Victoria; Scarpa, Ugo; Jankevics, Andris; Lloyd, Gavin; Southam, Andrew; Lee, Steven P; et al. (Blood, 2020)
Hematological and solid cancers catabolize the semiessential amino acid arginine to drive cell proliferation. However, the resulting low arginine microenvironment also impairs chimeric antigen receptor T cells (CAR-T) cell proliferation, limiting their efficacy in clinical trials against hematological and solid malignancies. T cells are susceptible to the low arginine microenvironment because of the low expression of the arginine resynthesis enzymes argininosuccinate synthase (ASS) and ornithine transcarbamylase (OTC). We demonstrate that T cells can be reengineered to express functional ASS or OTC enzymes, in concert with different chimeric antigen receptors. Enzyme modifications increase CAR-T cell proliferation, with no loss of CAR cytotoxicity or increased exhaustion. In vivo, enzyme-modified CAR-T cells lead to enhanced clearance of leukemia or solid tumor burden, providing the first metabolic modification to enhance CAR-T cell therapies.